Association of body mass index and psychological stress in medical students: a cross-sectional study - Mujeeb, Naushi; Lepcha, Chedup; Ailani, Vinita (International Journal of Research in Medical Sciences, 2025)
Background: Stressful life circumstances have many known negative implications on personal health. Medical students are especially exposed to very stressful life which may impact their health and behaviour. So, This study aimed to analyze the association between psychological stress and BMI in medical students in Sikkim. Methods: This cross-sectional study measured BMI and stress in 132 MBBS students from Sikkim, India between the age group of 18-26 years. The relation between them was analyzed using the student t-test and Pearson’s correlation. P value<0.05 was taken as significant. Results: Higher grades of BMI were associated with higher values of total stress, but the P value (0.85) was not significant. BMI and weight were also higher in groups with greater severity of stress (mild, moderate and severe), but the associations were not significant (p=0.035). Conclusions: This study shows no significant association between stress and BMI in medical students. However, higher BMI values were seen with increased total stress and the degree of stress. Further studies with larger sample sizes and diverse regions may provide a conclusive association between stress and BMI. Universities must adopt measures to minimize stress and stress-associated changes in BMI in medical students. Psychological and stress-related counselling should be given to at-risk students to prevent eating disorders.